What is the clinical impact of staging and surveillance PET‐CT scan findings in patients with bone and soft tissue sarcoma?. Issue 5 (13th January 2022) - Lee, Linus; Kazmer, Alexander; Colman, Matthew W.; Gitelis, Steven; Batus, Marta; Blank, Alan T.
Abstract: Background and Objectives: Positron emission tomography‐computerized tomography (PET‐CTs) are becoming increasingly utilized in sarcoma care, workup, and surveillance. This study aimed to describe additional PET‐CT findings as well as subsequent workups and changes in the clinical course due to those results. Methods: Patient records were retrospectively reviewed, and the additional workups and evaluations triggered by PET‐CT findings were qualitatively analyzed to document their results. Additional changes in the clinical course were documented. Results: A total of 183 bone and soft tissue sarcoma patients underwent PET‐CT as part of staging or surveillance. Additional workup was performed in 31.5% ( n = 41 of 130) patients who had positive PET‐CT findings. Among these, 36.6% ( n = 15 of 41) patients had clinically significant findings that altered the clinical course. Overall, 14.8% ( n = 27 of 183) experienced a change in the clinical course due to PET‐CT. Conclusion: PET‐CT often highlights lesions of potential clinical importance. Additional workup, as well as changes in the clinical course, were not infrequent. Future, multi‐institutional studies should address the value of PET‐CT in sarcoma care.